The impact of optimism on usage of computer based accounting practices among small scale enterprises - Rathnayake, R. M. M. P. (IJRDO - Journal of Applied Management Science, 2015)
In most parts of developed countries, it is almost impossible to function as an accountantwithout requisite Information Technology skills. Advent of the computerized accountingpractices equally affected to the organizations in both developed and developing countries.As introducing new technologies, the manual accounting systems have become graduallyinadequate for decision needs.The major objective of the research paper is to explore the impact of Optimism of smallbusiness owners on their Usage of Computer based Accounting Practices among small scalebusinesses. Moreover, it tries to evaluate the level of Optimism regarding the Technology andthe level of the Usage of Computer based Accounting Practices among small scalebusinesses. And ultimately it tries to find out the relationship between Optimism and theUsage of Computer based Accounting Practices among the small scale businesses.The study was conducted among the sample of hundred small business owners who wererandomly selected from Nuwara Eliya district. The data analysis included the Univariateanalysis (descriptive), Cross Tabulation analysis and Bivariate analysis. Considering thevariable, Usage of Computer Based Accounting Practices among small scale businesses inNuwara Eliya district is in low level but the influence of the Optimism regarding theTechnology is in high level. The Pearson‟s correlation analysis explores that there is apositively significant linear relationship between Optimism regarding the Technology and theUsage of Computer based Accounting Practices. Regression analysis has proved thatOptimism regarding the Technology of small business owners shall be considered as astrategic tool and major predictor of Usage of Computer based Accounting Practices amongsmall businesses in Nuwara Eliya district.